Docking Studies of Methylthiomorpholin Phenols (LQM300 Series) with Angiotensin-Converting Enzyme (ACE) - Vázquez-Valadez, Víctor H. (Bentham Open, 2013)
A main target in the treatment of hypertension is the angiotensin-converting enzyme (ACE). This enzyme is responsible for producing angiotensin II, a potent vasoconstrictor. Therefore, one of the targets in the treatment of hypertension is to inhibit ACE activity. Hence, this study’s aim is to use computational studies to demonstrate that the proposed heterocyclic compounds have a molecular affinity for ACE and that, furthermore, these heterocyclic compounds are capable of inhibiting ACE activity, thus avoiding the production of the vasopressor Angiotensin II. All this using computer-aided drug design, and studying the systems, with the proposed compounds, through molecular recognition process and compared with the compounds already on the market for hypertension.